The Effectiveness of Metacognitive Training on Distress Tolerance and Cognitive Dysregulation in Mothers of Children with Intellectual Disabilities - Zobeidizad, Khadijeh; Sattari, Fahimeh (Applied Family Therapy Journal (AFTJ), 2026)
Objective: The present study aimed to investigate the effectiveness of metacognitive training on distress tolerance and cognitive dysregulation in mothers of children with intellectual disabilities.Methods and Materials: This study was an applied quasi-experimental research with a pretest–posttest design and a two-month follow-up including a control group. The statistical population consisted of all mothers of children with intellectual disabilities in Tabriz in 2025, from whom 30 participants were selected using purposive and convenience sampling methods. After meeting the inclusion criteria and providing informed consent, participants were randomly assigned to an experimental group (n = 15) and a control group (n = 15). The experimental group received 12 weekly sessions of metacognitive training based on Wells’ protocol (2017), each lasting 60 minutes, while the control group received no intervention. Data were collected using the Distress Tolerance Questionnaire (Simons & Gaher, 2005) and the Cognitive Dysregulation Questionnaire (Mason et al., 1995), administered at pretest, posttest, and follow-up stages. Data were analyzed using repeated measures analysis of variance (ANOVA) in SPSS version 27.Findings: The results of repeated measures ANOVA indicated significant effects of time, group, and time × group interaction on distress tolerance (F = 195.32, p < .001, η² = 0.875; F = 45.94, p < .001, η² = 0.621; F = 71.43, p < .001, η² = 0.718) and cognitive dysregulation (F = 280.98, p < .001, η² = 0.909; F = 30.82, p < .001, η² = 0.524; F = 98.78, p < .001, η² = 0.779). Multivariate analysis of variance also confirmed a significant main effect of time (F = 31.86, p < .001, η² = 0.485) and a significant time × group interaction (F = 44.92, p < .001, η² = 0.581). Bonferroni post hoc tests showed significant differences between pretest and posttest and between pretest and follow-up (p < .001), while no significant differences were observed between posttest and follow-up (p = 1.00), indicating stability of effects.Conclusion: Metacognitive training is an effective and stable intervention for increasing distress tolerance and reducing cognitive dysregulation in mothers of children with intellectual disabilities, and its effects remain sustained over time.